Fecal bile acid dysmetabolism and reduced ursodeoxycholic acid correlate with novel microbial signatures in feline chronic kidney disease - Rowe, John C.; Summers, Stacie C.; Quimby, Jessica M.; Winston, Jenessa A. (Frontiers in Microbiology, 2024)
Background: Microbial-derived secondary bile acids (SBAs) are reabsorbed and sensed via host receptors modulating cellular inflammation and fibrosis. Feline chronic kidney disease (CKD) occurs with progressive renal inflammation and fibrosis, mirroring the disease pathophysiology of human CKD patients. Methods: Prospective cross-sectional study compared healthy cats (n = 6) with CKD (IRIS Stage 2 n = 17, Stage 3 or 4 n = 11). Single timepoint fecal samples from all cats underwent targeted bile acid metabolomics. 16S rRNA gene amplicon sequencing using DADA2 with SILVA taxonomy characterized the fecal microbiota. Results: CKD cats had significantly reduced fecal concentrations (median 12.8 ng/mg, Mann-Whitney p = 0.0127) of the SBA ursodeoxycholic acid (UDCA) compared to healthy cats (median 39.4 ng/mg). Bile acid dysmetabolism characterized by <50% SBAs was present in 8/28 CKD and 0/6 healthy cats. Beta diversity significantly differed between cats with <50% SBAs and >50% SBAs (PERMANOVA p < 0.0001). Twenty-six ASVs with >97% nucleotide identity to Peptacetobacter hiranonis were identified. P. hiranonis combined relative abundance was significantly reduced (median 2.1%) in CKD cats with <50% SBAs compared to CKD cats with >50% SBAs (median 13.9%, adjusted p = 0.0002) and healthy cats with >50% SBAs (median 15.5%, adjusted p = 0.0112). P. hiranonis combined relative abundance was significantly positively correlated with the SBAs deoxycholic acid (Spearman r = 0.5218, adjusted p = 0.0407) and lithocholic acid (Spearman r = 0.5615, adjusted p = 0.0156). Three Oscillospirales ASVs and a Roseburia ASV were also identified as significantly correlated with fecal SBAs. Clinical and Translational Importance: The gut-kidney axis mediated through microbial-derived SBAs appears relevant to the spontaneous animal CKD model of domestic cats. This includes reduced fecal concentrations of the microbial-derived SBA UDCA, known to regulate inflammation and fibrosis and be reno-protective. Microbes correlated with fecal SBAs include bai operon containing P. hiranonis, as well as members of Oscillospirales, which also harbor a functional bai operon. Ultimately, CKD cats represent a translational opportunity to study the role of SBAs in the gut-kidney axis, including the potential to identify novel microbial-directed therapeutics to mitigate CKD pathogenesis in veterinary patients and humans alike.